'We have the same enemies': Simone de Beauvoir and the silent feminism of C. Wright Mills. Issue 3 (1st September 2020) - Anderson, Patrick D.
ABSTRACT: During the last two decades, there has been a surge of interdisciplinary interest in the writings of the radical twentieth-century sociologist C. Wright Mills, and one of the central issues in this wave of scholarship has been the Mills' relationship to feminism and the place of sex and gender in his social theory. Contemporary scholars assert that Mills was largely ignorant about feminism or even hostile to it and that his social theory basically ignores issues of sex and gender. As this essay shows, the existing consensus is fundamentally mistaken. Mills' social theory of sex and gender and his emerging critique of patriarchy were heavily influenced by the 'silent feminists, ' Shira Tarrant's name for the leading women social scientists and philosophers of the 1930s and 40s. Though an analysis of Mills' Character and Social Structure and White Collar, I show that Mills' anti-essentialist conception of gender was inspired by the work of anthropologist Margaret Mead, sociologist Viola Klein, and psychoanalyst Karen Horney. Likewise, through an analysis of Mills' review of Simone de Beauvoir's The Second Sex, I show that not only is his critique of Beauvoir rooted in his readings of the silent feminists but also that Beauvoir's influence on Mills' thought can be traced through his most popular works, The Power Elite and The Sociological Imagination .